Implementasi Standar Proses Pembelajaran Pendidikan Agama Islam di Sekolah Menengah Pertama Negeri 6 Seluma - Nita Hartati; Mawardi Lubis; Desi Eka Citra (Journal on Education, 2023)
This study uses a qualitative approach and descriptive research type. Methods of data collection were carried out including using observation, interview, and documentation methods. The collected data is then selected and analyzed through; Data reduction; Presentation of Data and then Draw Conclusions. The results of this study indicate that: The standard implementation of the learning process for Islamic religious education at SMP Negeri 6 Seluma has been well implemented, which is based on the curriculum, syllabus and lesson plans. PAI teachers have carried out the planning of the learning process by carrying out preliminary activities, core activities and closing activities and the form of implementation is in the form of implementing the curriculum and learning process of Islamic Religious Education. The learning process for SMP Negeri 6 Seluma is always supervised by the school principal and the Seluma Education Office and PAI teachers who always give awards to students who excel. The impact of the standard implementation of the PAI learning process is that for students learning PAI is not boring, students are very happy to take part in PAI learning and students' interest in active learning is very high, this is evident from the fact that many students are happy to ask questions, always do homework and every explanation of the PAI teacher is always heard by students. The inhibiting factors in implementing the standard learning process for Islamic religious education at SMP Negeri 6 Seluma are the learning process which is very limited, the breadth and depth of the material to be delivered to students, the lack of experience of PAI teachers in teaching in class, the many differences in student characteristics, it is difficult to find methods appropriate in learning and still lacking educational infrastructure such as learning media in schools.